2013
DOI: 10.1007/s13224-013-0487-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overt and Subclinical Thyroid Dysfunction Among Pregnant Women and Its Effect on Maternal and Fetal Outcome

Abstract: Aim To determine the current prevalence of thyroid dysfunction in normal pregnant women and to study the impact of thyroid dysfunction on maternal and fetal outcome. Methods 400 pregnant women between 13 and 26 weeks of gestation were registered for the study. Apart from routine obstetrical investigations, TSH tests were done. Free T4 and anti-TPO antibody tests were done in patients with deranged TSH. Patients were followed up till delivery. Their obstetrical and perinatal outcomes were noted. Results The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
115
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(155 citation statements)
references
References 13 publications
(12 reference statements)
27
115
13
Order By: Relevance
“…In a study by Goldman C et al, the prevalence was 2.2% and another study by Ajmani et al, the prevalence was 9%. 3,5,6 In a study by Casey BM et al, the prevalence was 23% which is very high and inconsistent with our study. 7 In the present study, the prevalence of overt hypothyroidism was 1.6% which is comparable to the study by Cleary Goldman et al, where the prevalence was less than 1%.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In a study by Goldman C et al, the prevalence was 2.2% and another study by Ajmani et al, the prevalence was 9%. 3,5,6 In a study by Casey BM et al, the prevalence was 23% which is very high and inconsistent with our study. 7 In the present study, the prevalence of overt hypothyroidism was 1.6% which is comparable to the study by Cleary Goldman et al, where the prevalence was less than 1%.…”
Section: Discussioncontrasting
confidence: 99%
“…5,6 The prevalence of overt hypothyroidism was 2.9% and another study by Ajmani et al showed prevalence of 3%; whereas a study by Sahu MT showed a higher prevalence of 4.58%. 2,3 In this study, no significant association was observed between preterm labour hypothyroidism. The incidence of preterm labour in subclinical hypothyroidism was 5% and in overt hypothyroidism was 12.5%.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations